Quality evaluation of surrounding rocks in a mine shaft based on the game gray target model - Guo, Li-Ping; Gu, Xin-Bao (Frontiers in Earth Science, 2024)
Correct evaluation of surrounding rock quality grade can provide a safety guarantee for tunnel design and construction. So it has great significance for the construction of mine shaft. At first, the uniaxial saturated compressive strength of the rock block c R , rock quality index RQD , rock softening coefficient R k , integrity coefficient of rock mass v k , depth H , unit weight of rock mass  , coefficient of quantification about the angle between the principal structural plane and shaft axis 2k , and the weight of groundwater 1 k are selected as the assessment index;and the game-gray target model is introduced. Then, the gray target model of surrounding rocks in a mine shaft project is established. The weight coefficients of each index are calculated using the game combination weighting method, and each sample's synthetic target center distance is determined using the gray target model. Finally, the quality levels of the asphalt pavement are determined. The suggested model can mine the small sample data to the greatest extent and weaken the information shortage problem caused by the small sample to a certain extent. The final quality grade of surrounding rocks can be evaluated quantitatively. Therefore, it can provide a new approach and think for the future quality assessment of surrounding rocks.